DINAMIKA PEMILU SERENTAK 2024 - Raja Inal Dalimunthe (Jurnal Ilmu Hukum, 2023)
ABSTRACT In 2024 will be a spectacular political year in the history of democracy in Indonesia. General elections will be held in February 2024 to elect a president and vice president, members of the People's Representative Council (DPR RI), the Regional Representatives Council (DPD RI), and the Provincial and city-district Regional People's Representative Councils (DPRD). Meanwhile, Pilkada will be held in November 2024 to elect the Governor and Deputy Governor, regents and deputy regents, as well as mayors and deputy mayors throughout Indonesia. The implementation of simultaneous regional elections in 2024 is regulated in Article 201 Paragraph (8) of Law Number 10 of 2016 which states that simultaneous national voting in the election of governors and deputy governors, regents and deputy regents, as well as mayors and deputy mayors throughout the Republic of Indonesia will be held in November 2024. The research method used is library research. The results of this study indicate that First, the idea of ​​simultaneous General Elections when viewed through the original intent method and the science of historical (historical) interpretation, then its position has a constitutional juridical basis as an effort to shift the era of democratic transition towards democratic consolidation which emphasizes efforts to minimize bad practices a direct democratic system that is transactional, corrupt, and has a tendency to institutionalize clan politics in the dynamics of the constitutional political system in Indonesia. Second, in the practical realm it is actually counter-productive and inconsistent with efforts to uphold the law, strengthen the presidential system and constitutional supremacy because conditional constitutionality as set forth in the Decision tends to impede the realization of consolidation of democracy in the momentum of the General Elections in 2024. Keywords: Dynamic, concurrent election 0f 2024, Democracy.